Exploring the nexus of relevance for south african business schools in the 4th industrial revolution - Suleman, Aamir; Meyer, Natanya; Nieuwenhuizen, Cecile (Journal of Management and Business Education, 2023)
The world of work is changing at a rapid and alarming pace. These changes have been ushered by several factors, including new technologies due to the 4th industrial revolution, political instability such as the war in Ukraine and the global health crises due to the Covid-19 pandemic. These changes have resulted in an increasingly complex business operating environment, where leaders in the 4th industrial revolution are now facing challenges that previous generations have never encountered. Business schools have a strategic role in developing leaders fit for the 4th industrial revolution. Business schools have remained a steadfast pillar of strategic development across the world with the purpose of cultivating leaders that are able to achieve business success. However, in times of change, business schools need to adapt and align to ensure that they are cultivating leaders that are able and capable of navigating through the changing world of work. This study explored the relevance of South African business schools in programmes such as the MBA. This was done by conducting 30 in-depth qualitative interviews with key stakeholders related to the business school ecosystem. The findings of the interviews were coded, analysed and interpreted into a conceptual model documenting the nexus of relevance for South African business Schools. This model presents a conceptual framework which indicates that if a business school acts within the nexus of industry, society and government, it will remain relevant to key stakeholders in the business school ecosystem.